Serum total folate, 5‐methyltetrahydrofolate and vitamin B12 concentrations on incident risk of lung cancer. Issue 6 (12th October 2022) - Wei, Yaping; Xu, Benjamin; He, Qiangqiang; Chen, Ping; Zhang, Qi; Zhang, Xi; Yuan, Hui; Duan, Yong; Wang, Zhuo; Zhou, Ziyi; Liu, Lishun; Song, Yun; et al.
Abstract: Tobacco smoking is a major known risk factor for lung cancer. While micronutrients, especially those involved in maintaining DNA integrity and regulating gene expression, may be protective, research on this association is limited. This report aimed to investigate associations of total folate, 5‐methyltetrahydrofolate (5‐mTHF) and vitamin B12 with incident risk of lung cancer, and whether the associations vary by smoking status. A nested case‐control study with 490 incident lung cancer cases and 490 controls matched by age (±1 year), sex, residence, and center, drawn from a community‐based prospective study in China, was conducted from 2016 to 2019. 5‐mTHF accounted for the majority of total folate. Only 4.4% had detectable unmetabolized folic acid. Lung cancer cases had lower levels of 5‐mTHF compared to controls. There was an inverse, nonlinear association between 5‐mTHF and lung cancer, which persisted after adjustment for covariables ( P for trend = .001). Compared to the lowest 5‐mTHF quartile, those in higher quartiles had lower risks of lung cancer: second quartile OR = 0.65; 95% CI: 0.45‐0.93; third quartile OR = 0.50; 95% CI: 0.34‐0.74; fourth quartile OR = 0.56; 95% CI: 0.38‐0.83. This inverse association was more pronounced among ever smokers; consistently, the highest risk of lung cancer (OR = 3.21, 95% CI: 1.97‐5.24) was observed among ever smokers with low 5‐mTHF levels compared to participants who never smoked and had higher 5‐mTHF levels. Vitamin B12 was not associated with lung cancer risk. In this sample of Chinese adults without confounding by unmetabolized folic acid, higher levels of 5‐mTHF were associated with lower risk of incident lung cancer. Abstract : What's new? While micronutrients involved in one‐carbon metabolism, particularly folate, folate subtypes, and vitamin B12, are linked to reduced lung cancer risk, whether they protect against lung cancer remains unclear. In our study, total folate, 5‐methyltetrahydrofolate (5‐mTHF), and vitamin B12 were investigated for associations with lung cancer risk and smoking status. Lung cancer patients, notably ever smokers, were found to have low levels of 5‐mTHF. Moreover, analyses revealed an inverse, nonlinear relationship between 5‐mTHF levels and lung cancer, which was independent of homocysteine levels, vitamin B12 and other covariables. Meanwhile, no association was detected between lung cancer and vitamin B12 levels.